A Fully Automated Car Parking Lot - Normanyo, Erwin; Husinu, Francis; Fiona, Kumi Manel (JURNAL NASIONAL TEKNIK ELEKTRO, 2021)
Most car parking lots in the country have not been fully automated and many of them serve temporal, manual parking needs. A fully automated car parking lot assures of flexibility, improved efficiency and minimisation of manual tasks. In this paper, use was made of Siemens Step 7 PLC and WinCC Flexible Advanced software to design a fully automated car parking lot. The number of parking spaces available, the parking space number and position, arrival and departure times of cars and the time spent at the parking space are provided by the design. Simulations of designed system using Simatic PLC SIM confirmed the fulfillment of the design criteria and reliability of the developed flowcharts. Remote operator monitoring and control of the car parking lot has been actualised. Simulation results on the parking of six cars for a time duration of 0.5 hr, 1 hr, 1.5 hrs, 2 hrs, 2.5 hrs and 3 hrs, respectively yielded a total amount of GHÂ¢ 17.00. It stands to reason that hitherto existing manual car parking lots should be converted into the fully automated type using a PLC and an HMI workstation in order to bring orderliness and deserving responsibility to car parking in Ghana.